Design of a kit based on nano-fibrous cellulose film modified with ninhydrin and carboxymethyl cellulose for examining proline and the authentication of natural honey - Fatemeh Khakpour; Sajad Pirsa; Fatemeh Nejabi (Heliyon, 2025)
In this study, a proline-specific kit (color sensor) based on Nano fibrous cellulose modified with ninhydrin and carboxymethyl cellulose (Cel/NH/CMC) was designed to identify the authenticity of natural honey. The color, physicochemical and structural properties of the kit were investigated by SEM (Scanning Electron Microscopy), FTIR (Fourier Transform Infrared), XRD (X-ray Diffraction), etc. techniques. The designed kit was calibrated for proline and used for its measurement. SEM image of the cellulose film showed that this film has a fibrous structure and the cellulose fibers have an approximate diameter of 50–150 nm. FTIR results indicated suitable physical and electrostatic interactions between cellulose, ninhydrin and carboxymethylcellulose. XRD results showed that ninhydrin and carboxymethylcellulose reduced the crystallinity of cellulose film. Addition of ninhydrin and carboxymethylcellulose increased the thickness of the kits. With the increase of ninhydrin, the solubility of the kit decreased significantly (p < 0.05). Both parameters a∗ and b∗ tended towards more positive numbers with the addition of ninhydrin and carboxymethylcellulose. The kit shows high sensitivity in detecting proline, with detection limits reaching as low as 0.2 mg/g and a linear range spanning from 0.2 to 2 mg/g. Optimal kit was selected due to its balanced composition of ninhydrin and carboxymethyl cellulose, which enhanced both sensitivity and stability. The investigation of the repeatability of the kit response and the repeatability of the construction also confirmed the very high repeatability of the response of the designed kits (below 2 %) towards proline. The proline content in 6 natural honey samples was in the range of 0.3–0.66 mg/g, which confirmed the authenticity of 4 honey samples in terms of naturalness.